2019
DOI: 10.1111/ijcp.13460
|View full text |Cite
|
Sign up to set email alerts
|

Emerging risk factors associated with prevalence of hepatitis c virus infection among Nigerians: Findings from blood donors in an academic hospital, Enugu South‐Eastern Nigeria

Abstract: Aim In Nigeria, reports on the prevalence of Hepatitis C risk factors have not been clearly elucidated, we investigate the risk factors that influence the prevalence and how the difference in awareness level of risk factors screening across age groups contributes to the disease. Methods A total of 8790 aged 18‐55 years old, who attended the Department of Haematology and Blood Transfusion Services, University of Nigeria Teaching Hospital, Enugu were screened. Among them, 135 were diagnosed with hepatitis C infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We also detected antibodies to the hepatitis C virus in 1.73% of the study population. Recent studies conducted in various parts of Nigeria reported hepatitis C sero-prevalence rates that ranged from 0.5% to 3.0%, with an average of 1.73% [ 28 29 30 31 ]. This perfect concordance is again evidence of the high quality and reliability of the NAIIS study.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected antibodies to the hepatitis C virus in 1.73% of the study population. Recent studies conducted in various parts of Nigeria reported hepatitis C sero-prevalence rates that ranged from 0.5% to 3.0%, with an average of 1.73% [ 28 29 30 31 ]. This perfect concordance is again evidence of the high quality and reliability of the NAIIS study.…”
Section: Discussionmentioning
confidence: 99%
“…which the WHO define in absolute term as low income <$2/day. The minimum wage in Nigeria is N18,000/month which is approximately $108/ month and categorized as low income 54 . This may be the reason why the study population rely on alternative treatment such as spiritual healing and traditional native healers which are affordable.…”
Section: Discussionmentioning
confidence: 99%